Convective Entrainment Rates Estimated From Aura CO and CloudSat/CALIPSO Observations and Comparison With GEOS‐5. Issue 17 (2nd September 2019) - Stanfield, Ryan E.; Su, Hui; Jiang, Jonathan H.; Freitas, Saulo R.; Molod, Andrea M.; Luo, Zhengzhao Johnny; Huang, Lei; Luo, Ming
Abstract: Entrainment rate (λ) in convective parameterizations remains a sensitive parameter with much uncertainty in model simulations. This study estimates λ using carbon monoxide (CO) measurements jointly from the Microwave Limb Sounder and Tropospheric Emission Spectrometer onboard the Aura satellite, associated with deep convective cases identified by CloudSat and CALIPSO observations. CO is treated as a conserved quantity over convective transport time scales, and a simple entraining‐plume model is used to derive entrainment rates. The relationships of the observational estimates of λ as a function of convective height, environmental relative humidity, and convective available potential energy (CAPE) derived from Atmospheric Infrared Sounder data are compared with those from Goddard Earth Observing System Model (GEOS‐5) simulations. Bulk statistics of λ show that the values of λ are predominately below 20%/km for deep convection and the occurrence frequency of any λ decreases with increasing λ. Composite λ values are generally lower in the tropics compared to northern midlatitudes in both observations and the GEOS‐5 model. A decrease of λ with increasing convective height is found in both observations and model simulations. We also find that λ tends to decrease with increasing CAPE in the observation‐based λs and plume‐based GEOS‐5 λs, although the model given λs have a nonmonotonic relation with CAPE. The observed λs have a weak relation with lower‐to‐middle tropospheric relative humidity, while both GEOS‐5 plume‐based and given λ increase with increasing relative humidity. Key Points: Estimated and given entrainment rates are predominately less than 20%/km as frequency decreases with increasing entrainment rate Entrainment rate decreases with increasing cloud top height (CTH) or level of maximum detrainment (LMD) Plume estimates of entrainment rate decrease with increasing convective available potential energy (CAPE)